Dermal absorption of semivolatile organic compounds from the gas phase: Sensitivity of exposure assessment by steady state modeling to key parameters. (May 2017) - Pelletier, Maud; Bonvallot, Nathalie; Ramalho, Olivier; Blanchard, Olivier; Mercier, Fabien; Mandin, Corinne; Le Bot, Barbara; Glorennec, Philippe
Abstract: Recent research has demonstrated the importance of dermal exposure for some semivolatile organic compounds (SVOCs) present in the gas phase of indoor air. Though models for estimating dermal intake from gaseous SVOCs exist, their predictions can be subject to variations in input parameters, which can lead to large variation in exposure estimations. In this sensitivity analysis for a steady state model, we aimed to assess these variations and their determinants using probabilistic Monte Carlo sampling for 8 SVOCs from different chemical families: phthalates, bisphenols, polycyclic aromatic hydrocarbons (PAHs), organophosphorus (OPs), organochlorines (OCs), synthetic musks, polychlorinated biphenyls (PCBs) and polybromodiphenylethers (PBDEs). Indoor SVOC concentrations were found to be the most influential parameters. Both Henry's law constant (H) and octanol/water partition coefficient (Kow ) uncertainty also had significant influence. While exposure media properties such as volume fraction of organic matter in the particle phase (fom-part ), particle density (ρpart ), concentration ([TSP]) and transport coefficient (ɣd ) had a slight influence for some compounds, human parameters such as body weight (W), body surface area (A) and daily exposure (t) make a marginal or null contribution to the variance of dermal intake for a given age group. Inclusion of a parameter sensitivity analysis appears essential to reporting uncertainties in dermal exposure assessment. Highlights: Sensitivity analysis was conducted for 8 SVOCs with MC simulations. SVOC air concentration is the most influential variable parameter. Octanol-water partition coefficient and Henry's law constant are influent uncertain parameters. Influence of airborne particles characteristics and human parameters is minimal.